2011
DOI: 10.1080/15287394.2011.529061
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression in the Medulla Following Oral Infection of Cattle with Bovine Spongiform Encephalopathy

Abstract: The identification of variations in gene expression in response to bovine spongiform encephalopathy (BSE) may help to elucidate the mechanisms of neuropathology and prion replication and discover biomarkers for disease. In this study, genes that are differentially expressed in the caudal medulla tissues of animals infected with different doses of PrP(BSE) at 12 and 45 mo post infection were compared using array containing 24,000 oligonucleotide probes. Data analysis identified 966 differentially expressed (DE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…In cattle, orally infected with BSE agent (12 and 45 months post-infection), 101 DE genes in Peyer’s patch tissues [52] and 176 DE genes in medulla [53, 54] have been identified. These genes are mainly associated with the synapse function (e.g., tachykinin, synuclein, neuropeptide Y, cocaine, amphetamine-responsive transcript, and synaptosomal-associated protein 25 kDa); calcium ion regulation (e.g., parvalbumin, visinin-like, and cadherin); immune and inflammatory response (major histocompatibility complex (MHC) class II), and apoptosis (cholinergic receptor).…”
Section: Identification Of Candidate Genes Through Functional Genomicmentioning
confidence: 99%
See 1 more Smart Citation
“…In cattle, orally infected with BSE agent (12 and 45 months post-infection), 101 DE genes in Peyer’s patch tissues [52] and 176 DE genes in medulla [53, 54] have been identified. These genes are mainly associated with the synapse function (e.g., tachykinin, synuclein, neuropeptide Y, cocaine, amphetamine-responsive transcript, and synaptosomal-associated protein 25 kDa); calcium ion regulation (e.g., parvalbumin, visinin-like, and cadherin); immune and inflammatory response (major histocompatibility complex (MHC) class II), and apoptosis (cholinergic receptor).…”
Section: Identification Of Candidate Genes Through Functional Genomicmentioning
confidence: 99%
“…This study identified 190 DE transcripts from different pathways including neuroactive ligand–receptor interaction, regulation of the actin cytoskeleton, focal adhesion, SNARE interactions in vesicular transport, T-cell receptor signaling, calcium signaling, TGF-beta signaling, and MAPK signaling. Inaddition, the Tag profiling was successful in identifying additional pathways like ErbB signaling, the T cell receptor, the Wnt signaling, antigen processing, cytokine-cytokine receptor interaction, Gap junction, and the PPAR signaling as compared to the previous microarray studies on BSE-infected medulla tissues [53, 55]. The common DE genes detected in all these studies [52-55, 65] on cattle were: S100 calcium binding and Calmodulin; Prolactin-related protein; GTPase, IMAP family member, Histocompatibility complex, class II, Metallopeptidase and Myosin, Glutathione S transferase A, Aldo-Keto reductase family and Nuclear receptor subfamily group H.…”
Section: Identification Of Candidate Genes Through Functional Genomicmentioning
confidence: 99%
“…Detected changes in gene expression would also be expected to vary with the species examined. The investigation of the transcriptomes of scrapie infected Peyer's patches of sheep 17,18 and global approaches to caudal medulla tissues from cattle infected with bovine spongiform encephalopathy 19 have shown that 100-200 genes are significantly up-or downregulated. These results revealed that prion infection may cause dysfunction of several molecular networks, including extracellular matrix, cell adhesion, neuroactive ligand-receptor interaction, complement and coagulation cascades, MAPK signaling, neurodegenerative disorder, SNARE interactions in vesicular transport, and the transforming growth factor beta signaling pathways.…”
Section: Prion Protein Functions and Early Embryonic Development In Zmentioning
confidence: 99%
“…Several studies have been published on gene expression analysis concerning scrapie [12,18,19] but this kind of information about BSE has only been recently available [10,13-15,20]. In this paper a dynamical study of the evolution of the disease was performed by an oligonucleotide microarray genome wide gene expression analysis done on a well characterized transgenic mouse model of BSE on different time points of the disease.…”
Section: Introductionmentioning
confidence: 99%